Perencanaan dan Perancangan Pusat Pelatihan Sepak Bola di Kabupaten Badung: Bahasa Indonesia - Made Natha Sukma Arga; I Putu Hartawan; I Kadek Merta Wijaya; I Nyoman Gede Maha Putra; Kadek Putra Santika Narayana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Football is a popular sport in Indonesia, but experienced stagnation after Dutch colonialism due to lack of facilities and parental support. In Badung Regency, Bali Province, there has been an increase in the development of football, even though some clubs do not yet meet FIFA/PSSI standards. Of the 22 clubs, 18 have their own fields, but 4 clubs have to rent them. This affects player consistency and resource usage. Therefore, the construction of a football training center in Badung Regency is proposed to improve the facilities and quality of football in the area. This center will provide outdoor, indoor fields, changing rooms, fitness center, swimming pool, cafeteria and classrooms with modern designs that pay attention to functional and environmentally friendly aspects. It is hoped that this center will become an example for other regions in Indonesia and fulfill the community's needs in watching and developing football.